Impacts of Dam Removal on the Macrobenthos of the Elwha River Delta - Dunnell, Clementine (Friday Harbor Laboratories, 2012)
For almost a century, the Elwha River has been constrained by the Elwha and Glines Canyon dams, which have severely restricted the transport of fine sediment downriver. The dams are currently undergoing removal; it is the largest such project ever attempted in the United States. The purposes of this experiment were to identify the macrobenthos currently living on the subaqueous delta and determine the potential impacts of dam removal, and the ensuing sediment influx, on macrobenthic diversity. Samples of benthic organisms and sediment were collected from the delta floor, inventoried and analyzed, and the results mapped to find correlations between the two. The results showed patterns suggesting a correlation between grain size and diversity, with the greatest diversity at sites with high percentages of gravel, and the lowest diversity at sites with high percentages of mud. These findings demonstrate the importance of sediment size and sorting on the diversity of the Elwha delta. Given that the sediment in Lake Aldwell and Lake Mills is expected to continue traveling downstream, this information can be used to predict how the dam removal will impact macrobenthic communities on the delta, including economically important species such as clams, geoducks and crabs.
Keywords: Elwha delta, dam removal, sediment, macrobenthos, grain-size distribution